An Analysis Of Sharia Financial Literacy And Sharia Financial Inclusion In The Village Program Continuity (A Case Study of the Women Farmers Group of Puspa Mandiri in Gunungkarang Village, Bobotsari District, Purbalingga Regency) - Norailis Ab. Wahab; Yoiz Shofwa Shafrani; Desi Latifah (El-Jizya: Jurnal Ekonomi Islam, 2023)
The Women Farmers Group of Puspa Mandiri is a village program that aims to increase women's empowerment in Gunungkarang Village, Bobotsari District, Purbalingga Regency. In this group tfarmerhere are several problems such as the frequent errors in writing the nominal in financial statements and the lack of capital for managing crop yields. These two problems are related to the level of financial literacy and Sharia financial inclusion. Therefore, this study aims to analyze the level of financial literacy and Sharia financial inclusion in the Women Farmers Group of Puspa Mandiri. This research is included as a field research using a quantitative descriptive approach. The variables in this study are financial literacy and Sharia financial inclusion. The main instrument in this study is in the form of a questionnaire which was distributed to 23 respondents. The research data were analyzed using descriptive statistics. The results of calculating the index of each variable are then categorized according to the analysis using descriptive percentage table. The results show that the level of Sharia financial literacy in the Women Farmers Group of Puspa Mandiri was in the medium category (61.35%) and the Sharia financial inclusion was in the low category (29.92%). The problems that arise are related to the level of Sharia financial literacy and the inclusion of Sharia finance in Women Farmers Group or Kelompok Wanita Tani (KWT) which can threaten the sustainability of the Gunungkarang Village program.